2002
DOI: 10.1007/bf02967543
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression involved in brain metastasis from breast cancer using cDNA microarray

Abstract: These results suggest that cytokines produced by glial cells in vivo may contribute, in a paracrine manner, to the development of brain metastases from breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 13 publications
1
27
0
1
Order By: Relevance
“…It has also been observed that the release of cytokines by glial cells contributes to the growth and metastatic potential of tumor cells within brain tissue. 7 The MDA-MB-231 tumor line has been a wellestablished model for metastatic bone tumors after intracardiac injection, even though the development of tumors in other tissues has been observed. 12 It is notable that the manipulation of this line in an attempt to develop clones with more specificity to bone or brain required multiple passages through mice where tumors colonizing the bone or brain were harvested, expanded, and reinjected into new mice.…”
mentioning
confidence: 99%
“…It has also been observed that the release of cytokines by glial cells contributes to the growth and metastatic potential of tumor cells within brain tissue. 7 The MDA-MB-231 tumor line has been a wellestablished model for metastatic bone tumors after intracardiac injection, even though the development of tumors in other tissues has been observed. 12 It is notable that the manipulation of this line in an attempt to develop clones with more specificity to bone or brain required multiple passages through mice where tumors colonizing the bone or brain were harvested, expanded, and reinjected into new mice.…”
mentioning
confidence: 99%
“…Functional analysis indicated that metastatic colonization occurs as a result of the cancer cells' modification following interaction with the surrounding environment in the liver. Other investigators also reported similar results (16,33,34). Nishizuka et al (34) reported that cytokines produced by glial cells in vivo may contribute in a paracrine manner to the development of brain metastases from breast cancer cells.…”
Section: Discussionmentioning
confidence: 66%
“…Other investigators also reported similar results (16,33,34). Nishizuka et al (34) reported that cytokines produced by glial cells in vivo may contribute in a paracrine manner to the development of brain metastases from breast cancer cells. Metastatic colonization differs from growth in the primary lesion by its requirement for angiogenesis, and changes in the local microenvironment in metastatic lesions and stressful conditions.…”
Section: Discussionmentioning
confidence: 66%
“…Over the last few years, several studies have been conducted using microarray to identify i) genes related to the metastases of primary breast tumors (11), ii) genes expressed differentially between normal individuals and cancer patients (12) and iii) changes in the gene expression pattern before and after chemotherapy (13). However, no genome-wide studies conducted to date have been limited to cytokineassociated genes or designed to clarify the complex network and relationships of cytokines with tumor and immune cells.…”
Section: Introductionmentioning
confidence: 99%